Teachers’ Concern towards Schemes to Popularize Science in Delhi Schools - Varghese, Manoj; Kumar, Pamposh; Gore, Manish Mohan (Journal of Advanced Research in English & Education; Vol 6 No 2 (2021): Journal of Advanced Research in English & Education, 2022)
The aim of the present paper is to explore the understanding of science teachers towards scientific concepts, temper, perception and ambience in teaching and promoting science through various schemes. The study is conducted in Delhi schools owing to it being the frontrunner in popularising science and inculcating a scientific temper among school students. Efforts are on to Promote, Propagate and Popularise Science among senior secondary school students. Although, the Govt schemes are common for both private & Govt school students, the perceptions & prospects vary. Private schools have better facilities, ambience and technical support. Preliminary analysis show that interventions have yielded a mixed response to the desired results of developing scientific brains and mindset before leaving the schools. The objective is to identify the missing links/ gap areas to fulfill achieving goals of scientific interventions in senior secondary schools of Delhi. As per the SCERT initiative, a group of Science teachers was formed to share their experiences and improve the quality of teaching by sharing and learning mechanism. A new teaching pedagogy along with several training modules were developed by this group, which was useful in the local context. The data were collected with the help of questionnaire & the obtained data was analyzed by the descriptive percentage statistics. The findings of this pilot study states that several schemes and programmes are in place, but the scientific approach of teachers is limited to teaching the students for their exam and not to know its practical utility. Most of the scientific interventions are in an activity mode. A lot more needs to be done to develop a behavioural change in the society regarding scientific perspective and to achieve that, the school teachers as brand ambassadors can play a crucial role. Also, an ambience needs to be created which would evoke scientific curiosity among the mass. Although, huge investments have been made on the institutions and programmes to promote science, proportionately a lot of scope is there to popularise science at the school level to imbibe scientific values in the society. How to cite this article: Varghese M, Kumar P, Gore MM. Teachers’ Concern towards Schemes to Popularize Science in Delhi Schools. J Adv Res Eng & Edu 2021; 6(2): 12-18. DOI: https://doi.org/10.24321/2456.4370.202109